PENGARUH INTELLECTUAL CAPITAL TERHADAP PROFITABILITAS DAN KINERJA PASAR - Chrisnatty Chandra Dwipayani; Andri Prastiwi (Diponegoro Journal of Accounting, 2014)
This study aims to analyze the effects of Intellectual Capital to Profitability and Market Performance. Intellectual capital which consists of human capital efficiency (HCE), structural capital efficiency (SCE), and the capital employed efficiency (CEE) which uses a model Pulic - Value Added Intellectual Coefficients (VAICTM). Profitability is proxied by Return on Assets (ROA) and market performance is proxied by the Market to Book Value (MtBV). The research samples are the trade and services in the Indonesia Stock Exchange in 2009-2012. Based on purposive sampling method, samples obtained 51 companies . This study used multiple linear regression to analyze the data.   The results of this study indicate that intellectual capital (IC), structural capital efficiency (SCE), and capital employed efficiency (CEE) is significant positive effect on return on assets (ROA), but in human capital efficiency (HCE) is not significant and negative effect the return on assets (ROA). Furthermore , the results of research on the performance of the market is proxied by market to book (MtBV) indicates that intellectual capital (IC) , structural capital efficiency (SCE) , and the capital employed efficiency (CEE) is not positive and not significant effect on the market to book (MtBV). In contrast , human capital efficiency (HCE) a positive significant effect on the market to book value (MtBV).